3D numerical modelling of thermal shock assisted percussive drilling. (December 2020) - Saksala, Timo
Abstract: A 3D numerical study on thermal shock assisted percussive drilling is presented. The governing thermo-mechanical problem is solved with the finite element method. Rock failure due to mechanical and thermal loadings is described by a damage-viscoplasticity model. The bit-rock interaction and the thermal jet heating are solved with an explicit time marching scheme. In the numerical simulations, the percussion drilling action, i.e. the dynamic indentation, on Kuru granite with a special triple-button bit is simulated. The effect of confining and down-the-hole pressures, simulating deep well drilling, are tested with an initial borehole setting. Generally, heat shock treatment enhances the performance of percussive drilling by facilitating the interaction of the damage systems induced by adjacent buttons in both shallow and deep wells. However, down-the-hole pressure severely impedes both the thermally and mechanically induced damage.